2019
DOI: 10.1016/j.pec.2018.12.004
|View full text |Cite
|
Sign up to set email alerts
|

‘Very difficult for an ordinary guy’: Factors influencing the quality of treatment decision-making amongst men diagnosed with localised and locally advanced prostate cancer: Findings from a UK-wide mixed methods study

Abstract: , E. (2018). 'Very difficult for an ordinary guy': Factors influencing the quality of treatment decision-making amongst men diagnosed with localised and locally advanced prostate cancer: findings from a UK-wide mixed methods study. Patient Education and Counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…Interestingly, we observed that patients who completed clinic questionnaires placed greater importance on a wider range of symptoms and side effects in comparison to those who participated in the support group NGTs, whereas patients recruited from support groups also prioritised elements from the following domains: "Functionality & Day to Day Living"; "Relationships and Social Life"; and "Mood and Emotion" (supplementary file 2). This variation in prioritisation of HRQoL domains is in agreement with the wider evidence base that shows patients may have discrete information needs across their cancer journey, influenced by multiple factors including the different treatments available to patients throughout their illness; the life-limiting side effects these treatments can bring; and how they impact on a patient's support and care needs [42,43]. Clinicians need to be cognisant of patients' diverse and changing areas of importance, and more systematic gathering and exchange of information across the patient journey could better support dialogues as part of shared decision-making and supportive care.…”
Section: Key Findingssupporting
confidence: 78%
“…Interestingly, we observed that patients who completed clinic questionnaires placed greater importance on a wider range of symptoms and side effects in comparison to those who participated in the support group NGTs, whereas patients recruited from support groups also prioritised elements from the following domains: "Functionality & Day to Day Living"; "Relationships and Social Life"; and "Mood and Emotion" (supplementary file 2). This variation in prioritisation of HRQoL domains is in agreement with the wider evidence base that shows patients may have discrete information needs across their cancer journey, influenced by multiple factors including the different treatments available to patients throughout their illness; the life-limiting side effects these treatments can bring; and how they impact on a patient's support and care needs [42,43]. Clinicians need to be cognisant of patients' diverse and changing areas of importance, and more systematic gathering and exchange of information across the patient journey could better support dialogues as part of shared decision-making and supportive care.…”
Section: Key Findingssupporting
confidence: 78%
“…with poor quality of life, [2] adverse impacts on work, [3] and informational needs. [4][5][6] Informational needs span across diagnosis and treatment to treatment effects, expectations for progressive disease and symptom management. [4,5,7,8] Informational needs remain unmet in up to a half of patients, [9,10] continue after diagnosis, change over time, [9] are associated with lower physical, social and role functioning, higher levels of illness concern, [10] and ability to take part in treatment-decision making.…”
Section: Introductionmentioning
confidence: 99%
“…Although participants expressed that information about the diagnostic process and what to expect was important, some preferred the healthcare providers to make the decisions and keep the information at a basic level. Previous studies have found that not all patients desire to be involved in decisions about their treatment after being diagnosed with PCa [ 31 , 32 ]. Findings in the current study suggest that men will benefit from their individual information preferences and wishes for involvement being identified early in the diagnostic phase of PCa.…”
Section: Discussionmentioning
confidence: 99%